The role of opioid receptors in modulating Alzheimer’s Disease - Tanguturi, Parthasaradhireddy; Streicher, John M. (Frontiers in Pharmacology, 2023)
Alzheimer’s disease (AD) is a complex neurological disorder characterized by accumulation of amyloid plaques and neurofibrillary tangles. Long term investigation of AD pathogenesis suggests that β-site amyloid precursor protein [APP] cleaving enzyme 1 (BACE1) and γ-secretase enzymes promote the amyloidogenic pathway and produce toxic Aβ peptides that are predisposed to aggregate in the brain. Hence, the targeted inhibition of BACE1/γ-secretase expression and function is a promising approach for AD therapy. Several reports have suggested that the opioid family of G-protein coupled receptors modulate the etiology of AD progression. It has also been found that changes in the signaling pathways of opioid receptors increased the expression of BACE1 and γ-secretase, and is strongly correlated with abnormal production of Aβ and pathogenesis of AD. Thus, the opioid receptor family is a promising candidate for targeted drug development to treat AD. In this review, we outline the involvement and mechanisms of opioid receptor signaling modulation in Alzheimer’s Disease progression.